Síntesis coloidal (pH:8) de CdSe nanoestructurado y caracterización estructural por STM - Hernández-Colin, Salvador; Sánchez Legorreta, Gabriela; Rosendo-Francisco, Porfirio Domingo (Pädi Boletín Científico de Ciencias Básicas e Ingenierías del ICBI, 2025)
The study and creation of new nanostructured semiconductor materials are great importance in the science advances, in particular one of them is Cadmium Selenide (CdSe). This work reports the results of the colloidal synthesis of the nanostructured CdSe at pH:8. The samples were analyzed with scanning tunneling microscopy (STM), from which it was concluded that the material is an electronegative semiconductor and using FFT, two phases were identified: a cubic with an atomic packing factor (APF) equivalent to 69.12%, and hexagonal with an APF of 41.4%, it was also possible to identify the lattice parameters of each structure, among other physical parameters of the material. From these data, a complete discussion and analysis of the results is presented both in the laboratory and in Fourier space.